EROSION CHARACTERISTICS OF A MEDIUM SAND BREACHED EMBANKMENT (Malaysian Journal of Civil Engineering, 2018)
Embankment breaching dam studies have been carried out since 1980s and researchers who carried out physical experiments have contributed the understanding in the breaching process. This includes lacking in data and understanding in upgrading the breach models. Therefore, this study is to analyse erosion characteristics of a medium sand of embankment breaching due to overtopping and to produce the breached outflow hydrographs for different inflow rates. Parameters such as sediment sizes, embankment slope and inflow rates were applied to examine the effects of breach parameters towards the breaching process. Experimental works on the breaching embankment were conducted to collect data needed and a dimensional analysis was proposed to get relationship of the dominant parameters that affect the failure of the embankment. The result obtained was presented in hydrographs analysis and a combination of dimensionless group of breached erosion. The finding concluded that the finer sediment produces higher peak outflow compared to a medium sediment size and controlling parameters such as particle diameter, d50, velocity, ub, and water density, Ïw are the significant parameters that affect the process of embankment breached. It also observed that the velocity after the breaching process increases once the water flow through an embankment dam and it started to decrease after passing through the middle of embankment due to the large surface area.